Makna Dan Nilai Pancasila Dalam Bernegara, Bermasyarakat Dan Beragama - ahmad munawaru zaman (Jurnal Manajemen Dakwah, 2025)
Pancasila, as the foundation and ideology of the state, must be implemented in state, society, and religion. This study aims to analyze the implementation of Pancasila values in state, society, and religion. This study uses qualitative methods. Through this method, the researcher will collect data through interviews and documents. Subsequently, the data will be processed and analyzed. The results explain that Pancasila guides state, society, and religion. Pancasila serves as a middle ground in state, society, and religion. In practice, within state, society, and religion, there are some aspects that align with and contradict Pancasila.  Keywords: Pancasila, State, Religion, Society